APLIKASI SISTEM PAKAR MENDIAGNOSA PENYAKIT YANG DISEBEBKAN OLEH NYAMUK BERBASIS WEB (Information Technology and Telematics, 2013)
Abstrak   Mosquitoes  are  carriers  of  several  types  and  causes  of  diseases  such  as  malaria,  dengue  fever  (Dengue Haemorrhagic Fever), chikungunya and elephantiasis (filariasi). Some of the above diseases partly responsible for the large number of  deaths in  some  countries  are tropical and  subtropical  climates.  The  rate of growth  is  difficult to prevent mosquitoes and inadequate handling of victims exacerbate the number of cases that occur in diseases caused by mosquito bites. Cases that occur in diseases caused by mosquito bites almost always happens every year, because of the difficulty of breaking the chain of spread of these diseases. System  development  methods  used  in  this  study  is  an  expert  system  that  consists  of  the   identification, conceptualization, formalization, implementation, evaluation and development system. System  design using the Levelled DFD context diagram and consists of a Level 0 DFD and ERD. Creating a website using PHP programming and MySQL database. The end result of this research is the diagnosis expert system which is caused by mosquito web based can be used to solve the problem of the diagnosis of diseases caused by mosquitoes, because it can provide a diagnosis of any type of disease. Keyword: Sistem Pakar, Nyamuk, PHP, MySQL